High-Performance Metal–Chalcogen Batteries - Long Zhang (Batteries, 2023)
The rapid proliferation in the market for smart devices, electric vehicles, and power grids over the past decade has substantially increased the demand for commercial lithium-ion batteries (LIBs) [...]